PERLINDUNGAN HUKUM TERHADAP PEREMPUAN KORBAN PENYEBARLUASAN PORNOGRAFI DENGAN MOTIF BALAS DENDAM (REVENGE PORN) DI MEDIA SOSIAL - Anggriani, Jeani Aprilia; Shodiq, M. D.; Basuki, Basuki (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The phenomenon of the dissemination of pornographic content motivated by revenge (revenge porn) has become increasingly prevalent with the development of digital technology and social media in Indonesia. This pornography crime not only violates privacy but also constitutes a form of gender based violence that has serious impacts on the psychological, social, and economic well being of female victims. Although several regulations, such as the Electronic Information & Transactions Law (UU ITE) and the Pornography Law have been used to address this issue, the latter is not spesifically designed to regulate the dissemination of non consensual intimate content. This legal vacuum creates legal threats, difficulties in proving the truth, and a high risk of re-victimization for victims. This study analyze the handling of the crime of distributin grevenge pornography on social media and the legal protection for female victims of the distribution of revenge pornography on social media. The theories used in this study are legal protection theory and victimology theory. The method of research used is normative juridical legal research with a statutory, contextual, and case-based approach. Data were obtained through a literature review covering primary legal materials, secondary legal materials, and tertiary legal materials. Analyzed using grammatical, systematic, teleological, and official interpretation techniques. The results of this study empasizes the improtance of establishing specific regulations governing revenge porn, including the definiton of revenge porn, the element of non-consensual behavior, protection of victim identity, mechanisms for removing digital content, and the obligations of digital platforms to prevent the dissemination of content. A victim-centered approach is needed to promote comprehensive recovery and prevent discrimintion and negative stigma. Therefore, clearer, more assertive, and responsive legal reform is necessary to provide maximum protection for female victims of revenge pornography in Indonesia.